Predicting the risk for progression of acquired myopia in school-age children - T.E. Tsybulska; N.G. Zavgorodnia; O.E. Pashkova (Ukrainian Society of Ophthalmologists, 2018)
Background: Prediction of myopia progression in children is of practical relevance. Purpose: To develop a prediction table for comprehensive assessment of the risks for progression of acquired myopia in school-age children. Materials and Methods: One hundred and forty-four low myopic children (288 eyes) underwent the examination. Of these, 62 (124 eyes) had progressive myopia, and 82 (164 eyes) had stable myopia. Prediction of the risk of myopia progression in children was performed with the use of the Shigan technique for normalization of strongly intensive measures based on the probabilistic Bayesian approach. Results: Minimal and maximal values for prediction coefficients with regard to the most informative predictors for myopia progression were calculated, and the relevant prediction table was generated. The table included history-, accommodation-, and biometry-related predictors, as well as those related to the phenotypical signs of connective tissue dysplasia (CTD) as follows: history-related predictors: family history of myopia (PCmin, 1.249; PCmax, 4.34) and manifestations of myopia at age under 8 years (PCmin, 1.18; PCmax, 2.67); accommodation-related predictors: habitual accommodative tone ≥ 0.5 D (PCmin, 1.29; PCmax, 7.51), absolute reserve of accommodation < 1.5 D (PCmin, 1.25; PCmax, 4.6), relative reserve of accommodation < 1.0 D (PCmin, 1.3; PCmax, 7.94); ocular biometry-related predictors: corneal diameter > 12 mm (PCmin, 1.31; PCmax, 9.31), axial length of the eye > 25.0 mm (PCmin, 1.31; PCmax, 9.82), anterior chamber depth ≥ 4 mm (PCmin, 1.28; PCmax, 6.22), corneal hysteresis < 11.0 (PCmin, 1.21; PCmax, 3.29), corneal radius of curvature > 8 mm (PCmin, 1.17; PCmax, 2.5), corneal refractive power < 41.5 D (PCmin, 1.17; PCmax, 2.5), peripapillary retinal nerve fiber layer thickness (PCmin, 1.12; PCmax, 1.9), P < 0.05; CTD-related predictors: asthenic habitus (PCmin, 1.67; PCmax, 4.66), scoliosis and other postural anomalies (PCmin, 1.61; PCmax, 4.21), prominent venous network of the skin (PCmin, 1.75; PCmax, 5.97), cardiac valve prolapse and other minor cardiac anomalies (PCmin, 1.6; PCmax, 4.03), anomalies of tooth position and dentition (PCmin, 1.64; PCmax, 4.37), long digits (PCmin, 1.63; PCmax, 4.3), flat foot (PCmin, 1. 49; PCmax, 3.1), hypermobility of the joints (PCmin, 1.46; PCmax, 2.95), hyperelasticity of the skin (PCmin, 1.44; PCmax, 2.84), and congenital gallbladder anomalies (PCmin, 1.52; PCmax, 3.32), P < 0.05. The newly identified range for the risk of progression of myopia was subdivided into 3 equal sub-ranges (low, moderate and high likelihood for the risk, of 30.67-54.47, 54.48-78.27 and 78.28-102.08, respectively). Conclusion: The use of the prognostic table proposed allows easy identification of school-age myopic children at risk for the progression of myopia, with subsequent development of customized diagnosis and treatment plans.